An implantable system for In Vivo chronic electromyographic study in the larynx. Issue 5 (3rd January 2017) - Li, Yike; Huang, Shan; Zealear, David
ABSTRACT: Introduction : Electromyography (EMG) plays an important role in exploring the mechanisms of selective reinnervation. An implantable system can help provide chronological information regarding reinnervation of laryngeal muscles. This study was designed to develop an implantable system for repeated recordings of spontaneous and evoked EMG from laryngeal muscles. Methods : This implantable system has 4 bipolar stimulus cuffs for bilateral recurrent laryngeal nerves (RLNs) and superior laryngeal nerves (SLNs), and 4 EMG recording electrodes for bilateral vocal fold adductors (thyroarytenoid–lateral cricoarytenoid, TA‐LCA) and abductor (posterior cricoarytenoid, PCA) muscles. The system was implanted in 8 canines for up to 41 weeks. Results : The system showed good compatibility. Consistent EMG signals were recorded from both PCA and TA‐LCA muscles. Conclusion : We developed a long‐term implantable EMG system that is simple and capable of obtaining stable EMG recordings from canine laryngeal muscles with minimal risk of device breakage, trauma, or infection. Muscle Nerve 55: 706–714, 2017